Contact force-controlled high power short duration radiofrequency ablation enables efficient creation of roof line and anterior mitral line in course of low voltage areas. (19th May 2022) - Schreieck, J; Seizer, P; Duckheim, M; Scheckenbach, C; Gawaz, M; Heinzmann, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Linear ablation lines in the left atrium are questionable for treatment of atrial fibrillation (AF). In particular they are challenging, performed with limited success rate and are arrhythmogenic due to recurrence of conduction. Contact force (CF)-controlled high power short duration (HPSD) radiofrequency ablation (RFA) in areas of fibrosis may overcome these limitations. Purpose: We investigated the efficiency of contact force (CF)-controlled high power short duration (HPSD) radiofrequency ablation (RFA) for creation of linear lines in case of fibrotic areas in the anterior left atrium. Methods: In 530 consecutive patients (pts), age 65±9 years, paroxysmal AF in 45%, persistent AF in 55%, AF-re-ablation in 32% of pts, undergoing HPSD CF-controlled RF ablation of AF. Besides from pulmonary vein isolation (PVI) additional left atrial linear ablation in the anterior left atrium was performed in 28% of patients exclusively in case of low voltage areas in the course of the line or in case of re-ablation of prior performed lines. Fibrosis was defined by areas of less than 0.5mV signals in high density 3D microelectrode mapping. More than 5% low voltage was present in 46% of pts and more than 20% low voltage in 27% of pts. HPSD RF ablation was performed using a power of 50 Watt, duration 5-15s, with CF-controlled catheters, seeking for CF of 10-30g, and an interlesion distance of 6mm. Results: A anterior roof line between both upper pulmonary veins was performed in 25% of pts (n=133), and an anterior mitral line in 17% of pts (n=88). The anterior mitral line connected the superior mitral anulus with left upper, right upper PV or anywhere this the roof line depending on the distribution of low voltage areas. Overall success rate of bidirectional conduction block at the roof line was 92% and at the mitral line 94%. After remapping of gaps and re-ablation with conventional 35-40 Watt RF application of unlimited duration, success rate at the roof line improved to 98% and at the mitral line to 97%. No serious complications were associated with creation of these lines, especially, no pericardial tamponade occurred. Limited follow up will presented at the time of presentation. Conclusions: CF-controlled creation of ablation lines in the anterior left atrium (roof line and anterior mitral line) by HPSD RF ablation is very efficient and safe in case of areas of low voltage in the course of the linear ablation. In rare cases additional conventional RF application of unlimited duration becomes necessary to complete the lines supported by identification of gaps by high density 3D microelectrode mapping. This approach has the potential to improve efficacy of AF ablation in patients with atrial fibrosis. The hypothesis have to be proven by a prospective controlled study in the near future.